GAMBARAN COPING STRESS PADA PENDATANG BARU YANG TINGGAL DI LINGKUNGAN PADAT DAN BISING DI JAKARTA - Desy Kumala Sari; Defiana Gunawan; Ruth Panny Septiani (Psikoislamedia : Jurnal Psikologi, 2018)
This study intended to find out of the image of stress and coping strategies used to deal with stress in individuals who lives in noise and crowded environment in Jakarta. The hypothesis proposed in this study is that there is a positive relationship between the stress experienced by the individual so they have to perform various types of coping stress on noise and crowded environment. This research uses quantitative method with 30 participants, and qualitative method with 2 participants. The data retrieval procedure is performed using quantitative techniques by spreading the questionnaire ways of coping to some people who have similar criteria, and qualitative with interviews and observations to each subject. Based on the results of research, each subject claimed to experience stress due to live in noise and crowded environment, and it makes them do coping strategies for them to get used to such environment. Coping strategy used is emotion focused coping.